Optic disc drusen and family history of Glaucoma: results of a patient-directed survey - Gramer, Gwendolyn; Gramer, Eugen; Weisschuh, Nicole (Journal of glaucoma, 2017)
Purpose: Prospective evaluation of family history (FH) of glaucoma and FH of optic disc drusen (ODD) in patients with sonographically confirmed ODD. Patients and Methods: A total of 87 patients with ODD interviewed all their first-degree and second-degree relatives using a detailed questionnaire on whether an ophthalmologist had diagnosed or excluded glaucoma or ocular hypertension (OH). Using a second questionnaire, 62 of these patients also provided information about ODD in their FH. Control groups for FH of glaucoma consisted of 2170 patients with glaucoma or OH evaluated with the same methods and identical questions for FH of glaucoma in a previous study, and of 176 healthy individuals without glaucoma or ODD who were interviewed on family history of glaucoma. Results: Glaucoma in FH was significantly more frequent in patients with ODD with an incidence of 20.7% compared with healthy controls with an incidence of 2.8%, and half as frequent as in glaucoma patients with an incidence of 40%. ODD in FH were found in 9.7% of patients with ODD. Conclusions: As there is a high frequency of family history of glaucoma in patients with ODD, evaluation of FH of ODD and FH of glaucoma is essential in patients with ODD. Glaucoma in FH of ODD patients requires intraocular pressure monitoring and whenever deemed beneficial timely initiation of intraocular pressure-lowering therapy.
Gesehen am 27.04.2018